Is there scientific basis for the treatment of femoral fracture by hydrotherapy? An integrative review - Maia, Francisco Eudison da Silva (2016)
Introduction: A femoral fracture is complex due to its severity, rehabilitation time, and individual and socioeconomic repercussions. In this perspective, hydrotherapy is a treatment method that seeks better efficiency and functional gains in a shorter time. Objective: The aim of this article is to review carefully whether there is support in the literature for the use of hydrotherapy in this type of pathology. Method: This study is characterized as a literature review, based on publications in the period between 2000 and 2014, accepting as criteria for inclusion studies in Portuguese, English, and Spanish, irrespective of gender and age, using predetermined descriptors. Results: The current literature does not record results demonstrating the efficacy of hydrotherapy for patients with femur fracture. Conclusion: The use of hydrotherapy is still based on empirical knowledge and clinical experiences, which indicates a greater need for research on this subject.